Implementation of whole slide imaging in surgical pathology: A value added approach - Mike Isaacs; Jochen K Lennerz; Stacey Yates; Walter Clermont; Joan Rossi; John D Pfeifer (Elsevier, 2011)
Background: Whole slide imaging (WSI) makes it possible to capture images of an entire histological slide. WSI has established roles in surgical pathology, including support of off-site frozen section interpretation, primary diagnosis, educational activities, and laboratory quality assurance (QA) activities. Analyses of the cost of WSI have traditionally been based solely on direct costs and diagnostic accuracy; however, these types of analyses largely ignore workflow and cost issues that arise as a result of redundancy, the need for additional staffing, and customized software development when WSI is integrated into routine diagnostic surgical pathology. The pre-scan, scan, and post-scan costs; quality control and QA costs; and IT process costs can be significant, and consequently, pathology groups can find it difficult to perform a realistic cost-benefit analysis of adding WSI to their practice. Materials and Methods: In this paper, we report a "value added" approach developed to guide our decisions regarding integration of WSI into surgical pathology practice. The approach focuses on specific operational measures (cost, time, and enhanced patient care) and practice settings (clinical, education, and research) to identify routine activities in which the addition of WSI can provide improvements. Results: When applied to our academic pathology group practice, the value added approach resulted in expanded and improved operations, as demonstrated by outcome based measures. Conclusion: A value added can be used to perform a realistic cost-benefit analysis of integrating WSI into routine surgical pathology practice.